'Is it better not to know certain things?': views of women who have undergone non-invasive prenatal testing on its possible future applications. Issue 4 (24th January 2019) - Bowman-Smart, Hilary; Savulescu, Julian; Mand, Cara; Gyngell, Christopher; Pertile, Mark D; Lewis, Sharon; Delatycki, Martin B
Abstract : Non-invasive prenatal testing (NIPT) is at the forefront of prenatal screening. Current uses for NIPT include fetal sex determination and screening for chromosomal disorders such as trisomy 21 (Down syndrome). However, NIPT may be expanded to many different future applications. There are a potential host of ethical concerns around the expanding use of NIPT, as examined by the recent Nuffield Council report on the topic. It is important to examine what NIPT might be used for before these possibilities become consumer reality. There is limited research exploring views of women on possible future uses of NIPT, particularly those of women who have undergone NIPT. In this study, we examined the views of women who undertook NIPT previously on the acceptability of and interest levels in using NIPT for a number of current and possible future applications. These included several medical conditions encompassing psychiatric, neurodevelopmental and adult-onset conditions as well as non-medical traits such as intelligence. One thousand women were invited to participate and 235 eligible surveys were received. Women generally reported an interest in using NIPT for medical conditions that severely impacted quality of life and with an onset earlier in life and stressed the importance of the accuracy of the test. Concerns were raised about the use of NIPT for non-medical traits. Respondents indicated that termination of pregnancy was not their only reason for testing, particularly in the case of sex. These results can further inform the ethical debate around the increasing integration of NIPT into healthcare systems.